2014
DOI: 10.1136/amiajnl-2013-001875
|View full text |Cite
|
Sign up to set email alerts
|

Electronic medical records and physician stress in primary care: results from the MEMO Study

Abstract: Stress may rise for physicians with a moderate number of EMR functions. Time pressure was associated with poor physician outcomes mainly in the high EMR cluster. Work redesign may address these stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
260
6
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(276 citation statements)
references
References 22 publications
6
260
6
4
Order By: Relevance
“…[1][2][3][4][5][6] Not only has this negatively impacted job satisfaction for residents and attending physicians, 7,8 but it also may be significantly reducing available time for patient care and negatively impacting patient outcomes. 9,10 In a 2013 poll, 92% of residents reported that clinical documentation obligations are excessive, and 73% of residents reported compromises in patient care by these requirements.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Not only has this negatively impacted job satisfaction for residents and attending physicians, 7,8 but it also may be significantly reducing available time for patient care and negatively impacting patient outcomes. 9,10 In a 2013 poll, 92% of residents reported that clinical documentation obligations are excessive, and 73% of residents reported compromises in patient care by these requirements.…”
mentioning
confidence: 99%
“…[58,59] Since they derive much satisfaction from personal communication with patients, [60] this isolating effect of the EMR has heightened professional discontent. [61,62] The authors will, in a separate report, publish qualitative data highlighting the EMR as a stressor among respondents to the PRAWS baseline survey.…”
Section: Discussionmentioning
confidence: 99%
“…The tedious manipulation of EHRs to perform tasks that take more time discourages providers and distracts them from undertaking accurate and comprehensive documentation [4]. Hospital organizations that have increased their quality ratings and have prospered financially through campaigns to educate providers in the principles of comprehensive documentation have found that they are struggling to keep providers focused on documentation after the adoption of EHRs.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing physicians to complex and new electronic medical record systems significantly increased stress and burnout. Allowing physicians to be involved in the planning stages reduced this stress and burnout [4]. In addition to the chosen team of stakeholders and end users, a special question and answer panel with the medical staff was conducted to get the physicians on board with clinical documentation and EHR implementation.…”
Section: Problem Statementmentioning
confidence: 99%